The Influence of Brand Trust and Product Involvement on Brand Engagement : Study on Kamen Rarebali Customers - Dewa Ngakan Putu Haris Aricandra; Putu Saroyini Piartrini (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study confirms that brand trust and product involvement have an important role in increasing brand engagement among Kamen RareBali consumers. The analysis results show that brand trust has a significant positive effect, meaning that the higher the level of consumer trust in the brand, the greater their involvement with the brand, both through interactions on social media and product purchases. This is in line with the theory that trust in the brand is an important foundation in building loyalty and long-term relationships with consumers. Meanwhile, product involvement also shows a significant positive effect, indicating that consumers who feel more involved, interested, or care about the product tend to be more active in brand engagement . These findings indicate that Kamen RareBali needs a strategy that emphasizes improving consumer experience with the product, including through educational content, interactive promotions, and personalized services. Simultaneously, these two variables explain 63.1% of the variation in brand engagement , implying that other factors such as service quality, shopping experience, and communication strategy also influence consumer engagement. The practical implication is that companies should focus on building brand trust through positive reputation, testimonials, and transparency, as well as increasing product engagement through emotional experiences and meaningful interactions.